THE EFFECT OF PROBLEM BASED LEARNING (PBL) MODEL ON CRITICAL THINKING ABILITY AND STUDENT LEARNING OUTCOMES ON ECOSYSTEM MATERIALS IN SMA NEGERI 5 LANGSA - Rani Riska Marjanah Sri Jayanthi (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2022)
ABSTRACTProblem based learning is a model that can develop students in critical thinking and improve student learning outcomes, so that it can make students have an increased curiosity. Problem based learning models can make students think more than memorize, understand lessons better through discussion and can increase creativity. The purpose of this study was to determine the effect and how the results of the problem based learning model on critical thinking skills and student learning outcomes. The sample used was class X IPA 3 with a total of 27 students as the experimental class and class X IPA 2 with a total of 24 students as the control class. This study uses an experimental design, namely a quasi-experimental design, and data analysis using t-test. The results of the t-test indicate that there is an effect of the problem based learning model on critical thinking skills and student learning outcomes on ecosystem materials at SMA Negeri 5 Langsa where tcount ttable for critical thinking skills 8,901 2,009 and learning outcomes 4,821 2,009. Based on the results of the study, it can be concluded that the problem based learning model has an effect on critical thinking skills and student learning outcomes on ecosystem materials at SMA Negeri 5 Langsa. Through the problem based learning model, the value of critical thinking skills is 78.41 in the high category, and student learning outcomes are 79.05 in the good category.Keywords: Learning Outcomes, Critical Thinking Ability, Problem Based Learning